2015
DOI: 10.1016/j.jssr.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Teacher Professional Characteristics, School Environmental Factors, and State Testing Policy on Social Studies Educators’ Instructional Authority

Abstract: Knowledge of pedagogy and social studies content influences a teacher's decision making and helps teachers conduct sound instructional practices despite the influence of high-stakes testing policies. Using national data from the Survey of the Status of Social Studies (S4), this study examined the associations of teachers’ professional characteristics, school environmental factors, and state testing policy on self-reported levels of authority that secondary level social studies teachers (grades 6–12) hold over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…This confirms some teachers still have misconceptions about how they should use the guidebook. Thus, teachers have to be prepared to meet the guidebook outcomes and the needs of all children in their classrooms (Aldridge & Goldman, 2007;Hlebowitsh et al, 2013;Hong & Hamot, 2015;National Council of the Social Studies, 2007).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This confirms some teachers still have misconceptions about how they should use the guidebook. Thus, teachers have to be prepared to meet the guidebook outcomes and the needs of all children in their classrooms (Aldridge & Goldman, 2007;Hlebowitsh et al, 2013;Hong & Hamot, 2015;National Council of the Social Studies, 2007).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This research was rooted in the assumption that effective PD should improve teachers" instructional practices, which, by extension, should result in improved student outcomes. Both the literature and the results of this study have shown that teachers who have strong academic background, good content knowledge, and pedagogy in the area they teach tend to: (1) exercise instructional authority, (2) practice ambitious teaching, (3) exercise good instructional decision-making, (4) often choose a variety of instructional sources for instructional purposes, (5) expose students to a plethora of viewpoints and (6) have the skills to arouse students interests and critical thinking skills (Grant, 2007;Hong & Hamot, 2015;Salinas, 2006).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Extended PDs have the potential to unveil teachers" perception of the impact of the PD on their content knowledge and pedagogy. In addition, extended PDs increase the likelihood that teachers will conduct sound instructional practice irrespective of the economic, geographic and policy constructs that govern their schools (Grant, 2005;Hong & Hamot, 2015;National Council for the Social Studies, 2007).…”
Section: Why Is Pd a Necessity For In-service Teachers?mentioning
confidence: 99%
“…In extant social studies education research, institutional pressure to cover vast amounts of content and an attendant focus on testing and test results have been the most cited barriers to the implementation of ambitious instruction (Anderson & Cook, 2014, Gerwin & Visone, 2006Meuwissen, 2012). Hong and Hamot (2015), for example, used data from the national Survey of the Status of Social Studies to study the self-reported levels of instructional authority of social studies teachers in grades 6-12 (n=6,702). Results indicated that, in states with state-mandated social studies tests, teachers reported more restricted autonomy in selecting what and how to teach than teachers in states without such tests (Hong & Hamot, 2015).…”
Section: Institutional Factorsmentioning
confidence: 99%